The Role of Interpersonal Communication in Resolving the Impact of Miscommunication on Customer Relations Officer (CRO) Services at Daihatsu Narogong - Hafizzah, Nabila; Soelistyowati, Dinar (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research is motivated by the important role of interpersonal communication, especially that carried out by the Customer Relations Officer (CRO) at Daihatsu Narogong, in resolving miscommunication with customer at Daihatsu Narogong. This research aims to determine the role of interpersonal communication in resolving the impact of service miscommunication with customer relations officers at Daihatsu Narogong. The research method used is ad qualitative research method with a descriptive type, data writing techniques using observation, interviews, and documentation techniques obtained from respondents related to this research who were selected based on personal experience and data analysis using data reduction techniques, data presentation and drawing conclusions. The results of this research show the role of interpersonal communication in resolving the impact of customer relations officer (CRO) service miscommunication at Daihatsu Narogong. The role of interpersonal communication carried put in customer relations officer services is able to resolve miscommunication well and clearly. So customers at Daihatsu Narogong are very satisfied with the service provided when resolving miscommunication